Finding of Bov-B LINE retroelement in parthenogenetic and bisexual lizard species of the genus Darevskia (Lacertidae) - Martirosyan, I. A.; Korchagin, V. I.; Tokarskaya, O. N.; Darevsky, I. S.; Ryskov, A. P. (Russian journal of genetics, 2006)
The Bov-B LINE retrotransposon was first discovered in Ruminantia and was long considered to be specific for this order. Later, this mobile element was described in snakes and some lizard species. Analysis of phylogenetic relationships of Bov-B LINE elements from different ruminants, snakes, and lizard species led to the suggestion on horizontal transfer of this retrotransposon from Squamata to Ruminantia. In the Squamata group, Bov-B LINE element was found in all snakes and some lizard species examined. The element was not detected in the genomes of some species of the genera Lacerta and Podarcis. In the present study, using PCR amplification and sequencing of PCR products, Bov-B LINE element was identified in the genomes of parthenogenetic and bisexual species of the genus Darevskia (Lacertidae), as well as in such species as Lacerta agilis and Zootoca vivipara, where this retrotransposon had not been not detected before.